Double-coated modified positive electrode material as well as preparation method and application thereof

By using the preparation method of double-cover modified positive electrode material based on solid phase sintering and coating high-entropy oxide positive electrode material, the problems of low specific capacity and first-circle efficiency are solved, and performance improvement and circulation performance are achieved.

CN119673995APending Publication Date: 2025-03-21GEM WUXI ENERGY MATERIAL CO LTD

Patent Information

Application Number
CN202411807300.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The specific capacity and first-circuit efficiency of existing solid-phase sintered coated high-entropy oxide cathode materials are low, making it difficult to improve their performance on the basis of ensuring cyclic performance.

Method used

Using the preparation method of double-cover modified positive electrode material, a high-entropy oxide coating material is obtained through the first sintering treatment, and on this basis, a solvent-thermal reaction and a second sintering treatment are performed to form a double-cover structure.

Benefits of technology

It effectively improves the specific capacity and first-circle efficiency of the positive electrode material, while maintaining good cycling performance, solving the problem of low specific capacity and first-circle efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179598860000101
    Figure BDA0005179598860000101
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of lithium ion battery positive electrode materials, in particular to a double-coated modified positive electrode material and a preparation method and application thereof. The preparation method of the double-coated modified positive electrode material comprises the following steps: obtaining a positive electrode material and a high-entropy oxide; uniformly mixing the positive electrode material with the high-entropy oxide, and carrying out first sintering treatment to obtain a high-entropy oxide coating material; and mixing the high-entropy oxide coating material, a carbon source and a solvent, and sequentially carrying out solvothermal reaction and secondary sintering treatment to obtain the double-coating modified positive electrode material. On the basis of carrying out high-entropy oxide solid-phase sintering coating modification on the positive electrode material, wet-process carbon coating is further carried out, so that the lithium-hydrogen exchange side reaction caused by long-time contact between positive electrode particles and a solution can be effectively reduced, and the defects of low specific capacity and low first-circle efficiency of the solid-phase sintering coating high-entropy oxide positive electrode material can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to a double-coated modified positive electrode material and a preparation method and application thereof. Background Art

[0002] Ternary lithium batteries have become the mainstream product of automotive batteries due to their advantages in energy density. At the same time, high-nickel and low-cobalt ternary materials, one of the positive electrode materials of ternary lithium batteries, have developed rapidly due to their high theoretical specific capacity. Ternary materials are usually composed of micron-sized secondary particles (about 1-30μm) composed of densely arranged submicron-sized primary particles (about 50-300nm) (i.e., polycrystalline crystal structure), but their specific capacity and cycle life are easily affected by structural damage caused by factors such as reactions and phase changes during charging and discharging, mechanical instability between and within primary particle crystals, and oxygen precipitation. At the same time, high-nickel and low-cobalt ternary positive electrode materials are more affected by the above factors due to the lack of stabilizing effect of cobalt. Some functional doping materials and coating materials can improve the above problems to increase the specific capacity and cycle life of positive electrode materials, for example, high entropy oxides (a single-phase solid solution formed by solid solution of multiple elements in equiatomic or near-atomic ratios).

[0003] At present, the existing high entropy oxide coating methods mainly include co-precipitation method and solid-phase sintering coating method. Among them, the co-precipitation method is not only easy to produce a large amount of wastewater, but also easy to cause structural damage to the surface of the positive electrode material particles mainly due to delithiation, so that the electrochemical performance of the positive electrode material after coating is still poor; although the solid-phase sintering coating method can avoid the structural damage to the surface of the positive electrode material particles mainly due to delithiation caused by the co-precipitation method, thereby improving the electrochemical performance of the positive electrode material (for example, cycle performance). However, the solid-phase sintering coated high entropy oxide positive electrode material still has the problem of low specific capacity and first-cycle efficiency. In this regard, how to improve the specific capacity and first-cycle efficiency of the solid-phase sintering coated high entropy oxide positive electrode material on the basis of ensuring the good cycle performance of the solid-phase sintering coated high entropy oxide positive electrode material is still an urgent problem to be solved. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of low specific capacity and low first-cycle efficiency of existing solid-phase sintered coated high-entropy oxide positive electrode materials, thereby providing a double-coated modified positive electrode material and its preparation method and application to solve the above problems.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a double-coated modified positive electrode material, comprising:

[0007] Obtaining cathode materials and high entropy oxides;

[0008] The positive electrode material and the high entropy oxide are mixed and subjected to a first sintering treatment to obtain a high entropy oxide coating material;

[0009] The high entropy oxide coating material, carbon source and water are mixed and subjected to solvent thermal reaction and a second sintering treatment in sequence to obtain a double-coated modified positive electrode material.

[0010] Preferably, the process of obtaining the positive electrode material comprises: mixing a lithium source and a ternary precursor and performing a first calcination treatment to obtain the positive electrode material;

[0011] And / or, the process of obtaining the high entropy oxide includes: mixing five or more metal oxides (in an equimolar ratio of alloy elements) and performing a second calcination treatment to obtain the high entropy oxide.

[0012] Preferably, the lithium source comprises lithium hydroxide monohydrate;

[0013] And / or, the ternary precursor is a nickel-cobalt-manganese ternary precursor; preferably, the molar amount of nickel element in the nickel-cobalt-manganese ternary precursor accounts for more than 90% of the total molar amount of metal elements in the nickel-cobalt-manganese ternary precursor;

[0014] and / or, the average particle size of the ternary precursor is 2-15 μm, preferably 2-8 μm;

[0015] And / or, the molar ratio of lithium in the lithium source to the metal element in the ternary precursor is (1.02-1.08):1.

[0016] Preferably, the metal oxide includes nickel oxide, cobalt oxide, manganese oxide, iron oxide, copper oxide, chromium oxide, titanium oxide, magnesium oxide, zinc oxide, aluminum oxide, zirconium oxide, tantalum oxide, niobium oxide, and hafnium oxide;

[0017] And / or, the temperatures of the first calcination treatment and the second calcination treatment are each independently selected from 750-900°C;

[0018] And / or, the atmosphere of the first calcination treatment and the second calcination treatment is an oxygen-containing atmosphere, preferably oxygen;

[0019] And / or, the duration of the first calcination treatment and the second calcination treatment are each independently selected from 5-15h;

[0020] and / or, after the first calcination treatment and the second calcination treatment, the positive electrode material and the high entropy oxide are crushed and sieved respectively;

[0021] And / or, a metal additive is also added during the process of obtaining the positive electrode material.

[0022] Preferably, the metal additive includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, molybdenum oxide, tantalum oxide, and tungsten oxide;

[0023] And / or, based on the mass of the ternary precursor being 600 g, the amount of the additive used is 2-10 g.

[0024] Preferably, the mass ratio of the positive electrode material to the high entropy oxide is 100:(0.5-2);

[0025] And / or, the temperature of the first sintering treatment and the second sintering treatment are each independently selected from 400-600° C.;

[0026] And / or, the duration of the first sintering treatment and the second sintering treatment are each independently selected from 4-10 hours;

[0027] And / or, the atmosphere of the first sintering treatment is an oxygen-containing atmosphere, preferably air;

[0028] And / or, the atmosphere of the second sintering treatment is an inert atmosphere, preferably nitrogen.

[0029] Preferably, the carbon source comprises glucose;

[0030] And / or, the solvent includes at least one of water, methanol and ethanol;

[0031] And / or, the mass ratio of the high entropy oxide coating material, the carbon source, and the solvent is 1: (0.005-0.02): (0.4-0.8);

[0032] and / or, the temperature of the solvent thermal reaction is 150-200° C.;

[0033] And / or, the duration of the solvent thermal reaction is 20-60 min;

[0034] And / or, the solvent thermal reaction is followed by solid-liquid separation and drying.

[0035] Preferably, the temperature of the drying treatment is 80-150°C.

[0036] In a second aspect, the present invention further provides a double-coated modified positive electrode material, which is prepared by the above-mentioned preparation method of the double-coated modified positive electrode material.

[0037] In a third aspect, the present invention also provides the use of the above-mentioned double-coated modified positive electrode material in a lithium-ion battery.

[0038] In the present invention, when the temperature and duration of the first calcination treatment and the second calcination treatment are the same, they are sintered in different saggers in the same furnace to reduce energy consumption.

[0039] In the present invention, the high entropy oxide is calcined with multiple metal elements in equal atomic ratios.

[0040] The technical solution of the present invention has the following advantages:

[0041] A preparation method of a double-coated modified positive electrode material, comprising: obtaining a positive electrode material and a high entropy oxide; mixing the positive electrode material and the high entropy oxide and performing a first sintering treatment to obtain a high entropy oxide coating material; mixing the high entropy oxide coating material, a carbon source, and water and sequentially performing a solvothermal reaction and a second sintering treatment to obtain a double-coated modified positive electrode material. The present invention further performs wet carbon coating on the basis of solid-phase sintering coating modification of the positive electrode material, which can effectively reduce the lithium-hydrogen exchange side reaction caused by long-term contact between the positive electrode particles and the solution, and can make up for the defects of low specific capacity and first-cycle efficiency of the solid-phase sintered coated high entropy oxide positive electrode material, and solves the problems of low specific capacity and first-cycle efficiency of the solid-phase sintered coated high entropy oxide positive electrode material on the basis of ensuring good cycle performance. DETAILED DESCRIPTION

[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0044] Example 1

[0045] This embodiment provides a method for preparing a double-coated modified positive electrode material, and the specific steps are as follows:

[0046] 1) 282.61 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02A (OH)2 ternary precursor, 3.402 g zirconium oxide, and 0.800 g yttrium oxide are mixed in a high-speed mixer; zirconium oxide, cobalt oxide, manganese oxide, iron oxide, titanium oxide, and magnesium oxide for high entropy oxide are mixed in a high-speed mixer according to a molar ratio of Zr:Co:Mn:Fe:Ti:Mg=1:1:1:1:1:1, and the two mixtures are respectively packed in different saggers and placed in the same muffle furnace, and sintered in an oxygen atmosphere at 850°C for 10 hours, and then crushed and sieved through a 325-mesh sieve to obtain a positive electrode material and a high entropy oxide;

[0047] 2) Weigh 600 g of the positive electrode material and 6 g of the high entropy oxide obtained in step 1) and mix them evenly in a high-speed mixer, then place the mixed material in a muffle furnace, sinter it under compressed air at 500° C. for 6 h, and obtain a high entropy oxide-coated positive electrode material after natural cooling in the furnace.

[0048] 3) 500 g of high entropy oxide coated positive electrode material, 5 g of glucose and 300 g of water were placed in a sealed pressure reaction tank, reacted at 180°C for 40 min, filtered and separated, dried at 120°C, then placed in a muffle furnace, and sintered again at 500°C for 6 h under nitrogen conditions. After natural cooling in the furnace, a double-coated modified positive electrode material was obtained.

[0049] Example 2

[0050] This embodiment provides a method for preparing a double-coated modified positive electrode material, and the specific steps are as follows:

[0051] 1) 293.53 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 0.80g magnesium oxide, and 1.20g aluminum oxide are mixed in a high-speed mixer; titanium oxide, magnesium oxide, zinc oxide, aluminum oxide, zirconium oxide, and niobium oxide for high entropy oxide are mixed in a high-speed mixer according to a molar ratio of Ti:Mg:Zn:Al:Zr:Nb=1:1:1:1:1:1, and the two mixtures are respectively packed in different saggers and placed in the same muffle furnace, and sintered in an oxygen atmosphere at 750°C for 15h, and then crushed and passed through a 325-mesh sieve to obtain a positive electrode material and a high entropy oxide;

[0052] 2) Weigh 600 g of the positive electrode material and 3 g of the high entropy oxide obtained in step 1) and mix them evenly in a high-speed mixer, then place the mixed material in a muffle furnace, sinter it under compressed air at 400° C. for 10 h, and obtain a high entropy oxide-coated positive electrode material after natural cooling in the furnace.

[0053] 3) 500 g of high entropy oxide coated positive electrode material, 10 g of glucose and 400 g of water were placed in a sealed pressure reaction tank, reacted at 200 ° C for 20 min, filtered and separated, dried at 80 ° C, and then placed in a muffle furnace and sintered again under nitrogen and 400 ° C for 10 h. After natural cooling in the furnace, a double-coated modified positive electrode material was obtained.

[0054] Example 3

[0055] This embodiment provides a method for preparing a double-coated modified positive electrode material, and the specific steps are as follows:

[0056] 1) 277.23 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 5.30g lanthanum oxide, and 7.20g molybdenum oxide are mixed in a high-speed mixer; zirconium oxide, cobalt oxide, manganese oxide, iron oxide, titanium oxide, and magnesium oxide for high entropy oxide are mixed in a high-speed mixer according to a molar ratio of Zr:Co:Mn:Fe:Ti:Mg=1:1:1:1:1:1, and the two mixtures are respectively packed in different saggers and placed in the same muffle furnace, and sintered in an oxygen atmosphere at 900°C for 5h, and then crushed and passed through a 325-mesh sieve to obtain a positive electrode material and a high entropy oxide;

[0057] 2) Weigh 600 g of the positive electrode material and 12 g of the high entropy oxide obtained in step 1) and mix them evenly in a high-speed mixer, then place the mixed material in a muffle furnace, sinter it under compressed air at 600° C. for 4 h, and obtain a high entropy oxide-coated positive electrode material after natural cooling in the furnace.

[0058] 3) 500 g of high entropy oxide coated positive electrode material, 2.5 g of glucose and 200 g of water were placed in a sealed pressure reaction tank, reacted at 150 ° C for 60 min, filtered and separated, dried at 150 ° C, and then placed in a muffle furnace and sintered again at 600 ° C for 4 h under nitrogen conditions. After natural cooling in the furnace, a double-coated modified positive electrode material was obtained.

[0059] Comparative Example 1

[0060] This comparative example provides a method for preparing a high entropy oxide coated modified positive electrode material, and the specific steps are as follows:

[0061] 1) 282.61 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02A (OH)2 ternary precursor, 3.402 g zirconium oxide, and 0.800 g yttrium oxide are mixed in a high-speed mixer; zirconium oxide, cobalt oxide, manganese oxide, iron oxide, titanium oxide, and magnesium oxide for high entropy oxide are mixed in a high-speed mixer according to a molar ratio of Zr:Co:Mn:Fe:Ti:Mg=1:1:1:1:1:1, and the two mixtures are respectively packed in different saggers and placed in the same muffle furnace, and sintered in an oxygen atmosphere at 850°C for 10 hours, and then crushed and sieved through a 325-mesh sieve to obtain a positive electrode material and a high entropy oxide;

[0062] 2) Weigh 600 g of the positive electrode material and 6 g of high entropy oxide obtained in step 1) and mix them evenly in a high-speed mixer, then place the mixed material in a muffle furnace, sinter it under compressed air at 500° C. for 6 h, and obtain a high entropy oxide-coated modified positive electrode material after natural cooling in the furnace.

[0063] Comparative Example 2

[0064] This comparative example provides a method for preparing a carbon-coated modified positive electrode material, and the specific steps are as follows:

[0065] 1) 282.61 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02 The (OH)2 ternary precursor, 3.402 g of zirconium oxide, and 0.800 g of yttrium oxide are mixed in a high-speed mixer to obtain a mixture; the mixture is placed in a muffle furnace, sintered at 850°C in an oxygen atmosphere for 10 hours, and then crushed and passed through a 325-mesh sieve to obtain a positive electrode material;

[0066] 2) 500 g of positive electrode material, 5 g of glucose and 300 g of water were placed in a sealed pressure reaction tank, reacted at 180°C for 40 min, filtered and separated, dried at 120°C, then placed in a muffle furnace, and sintered again at 500°C for 6 h under nitrogen conditions. After natural cooling in the furnace, a carbon-coated modified positive electrode material was obtained.

[0067] Comparative Example 3

[0068] This comparative example provides a method for preparing a double-coated modified positive electrode material, and the specific steps are as follows:

[0069] 1) 282.61 g of lithium hydroxide monohydrate and 600 g of Ni 0.92 Co 0.06 Mn 0.02A (OH)2 ternary precursor, 3.402 g zirconium oxide, and 0.800 g yttrium oxide are mixed in a high-speed mixer; zirconium oxide, cobalt oxide, manganese oxide, iron oxide, titanium oxide, and magnesium oxide for high entropy oxide are mixed in a high-speed mixer according to a molar ratio of Zr:Co:Mn:Fe:Ti:Mg=1:1:1:1:1:1, and the two mixtures are respectively packed in different saggers and placed in the same muffle furnace, and sintered in an oxygen atmosphere at 850°C for 10 hours, and then crushed and sieved through a 325-mesh sieve to obtain a positive electrode material and a high entropy oxide;

[0070] 2) Weigh 600 g of the positive electrode material and 6 g of the high entropy oxide obtained in step 1) and mix them evenly in a high-speed mixer, then place the mixed material in a muffle furnace, sinter it under compressed air at 500° C. for 6 h, and obtain a high entropy oxide-coated positive electrode material after natural cooling in the furnace.

[0071] 3) 500 g of high entropy oxide coated positive electrode material and 5 g of glucose were mixed in a high-speed mixer, and then placed in a muffle furnace, and sintered again under nitrogen and 500°C for 6 h. After natural cooling in the furnace, a double-coated modified positive electrode material was obtained.

[0072] Test Example 1

[0073] The finished coated modified positive electrode material prepared in the embodiment and the comparative example was used to prepare a lithium ion battery (CR2032 type button half-cell), and the specific method was as follows:

[0074] The mass ratio of positive electrode material: carbon black: PVDF is 90:5:5, and N-methylpyrrolidone is used as a dispersant (the amount of dispersant is 10 times the mass of PVDF). The positive electrode slurry is prepared and placed in a centrifuge for 30 minutes. The positive electrode slurry is evenly scraped and applied on the carbon-coated aluminum foil (the coating amount is 6 mg / cm 2 ), dried in an oven at 100°C for 2h to obtain a dried electrode. The dried electrode was rolled with a roller press at 40kN, and then dried in an oven at 100°C for 2h, and finally cut with a corresponding size grinder to obtain a positive electrode (a disc with a diameter of 1.3cm).

[0075] In the argon atmosphere of the glove box, Celgard 2500 diaphragm, lithium metal sheet as negative electrode, LBC3021C011 electrolyte were used. The battery was assembled in the order of negative electrode, electrolyte (the electrolyte was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (mass ratio was 1:1)), diaphragm, electrolyte, and positive electrode, and then placed in the blue electric test system for electrical performance testing.

[0076] The electrical performance test parameters are set as follows: at a temperature of 25°C, first charge to 4.25V at a rate of 0.2C, then discharge to 2.8V at a rate of 0.2C. This is a cycle process. The charge and discharge capacity this time is the first charge and discharge specific capacity, and the charge and discharge ratio is the first efficiency. After 2 cycles, charge at 0.5C and discharge at 1C for 50 cycles, record the charge and discharge capacity of the 3rd cycle and the charge and discharge capacity of the 52nd cycle, and the retention rate is the ratio of the discharge capacity of the 52nd cycle to the 3rd cycle. The test results are shown in Table 1.

[0077]

[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a double-coated modified positive electrode material, characterized in that: include: Obtaining cathode materials and high entropy oxides; The positive electrode material and the high entropy oxide are mixed and subjected to a first sintering treatment to obtain a high entropy oxide coating material; The high entropy oxide coating material, carbon source and solvent are mixed and subjected to solvent thermal reaction and a second sintering treatment in sequence to obtain a double-coated modified positive electrode material.

2. The preparation method according to claim 1, characterized in that: The process of obtaining the positive electrode material comprises: mixing the lithium source and the ternary precursor and performing a first calcination process to obtain the positive electrode material; And / or, the process of obtaining the high entropy oxide includes: mixing five or more metal oxides and performing a second calcination treatment to obtain the high entropy oxide.

3. The preparation method according to claim 2, characterized in that: The lithium source includes lithium hydroxide monohydrate; And / or, the ternary precursor is a nickel-cobalt-manganese ternary precursor; preferably, the molar amount of nickel element in the nickel-cobalt-manganese ternary precursor accounts for more than 90% of the total molar amount of metal elements in the nickel-cobalt-manganese ternary precursor; and / or, the average particle size of the ternary precursor is 2-15 μm, preferably 2-8 μm; And / or, the molar ratio of lithium in the lithium source to the metal element in the ternary precursor is (1.02-1.08):

1.

4. The preparation method according to claim 2 or 3, characterized in that: The metal oxides include nickel oxide, cobalt oxide, manganese oxide, iron oxide, copper oxide, chromium oxide, titanium oxide, magnesium oxide, zinc oxide, aluminum oxide, zirconium oxide, tantalum oxide, niobium oxide, and hafnium oxide; And / or, the temperatures of the first calcination treatment and the second calcination treatment are each independently selected from 750-900°C; And / or, the atmosphere of the first calcination treatment and the second calcination treatment is an oxygen-containing atmosphere, preferably oxygen; And / or, the duration of the first calcination treatment and the second calcination treatment are each independently selected from 5-15h; and / or, after the first calcination treatment and the second calcination treatment, the positive electrode material and the high entropy oxide are crushed and sieved respectively; And / or, a metal additive is also added during the process of obtaining the positive electrode material.

5. The preparation method according to claim 4, characterized in that: The metal additive includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, molybdenum oxide, tantalum oxide, and tungsten oxide; And / or, based on the mass of the ternary precursor being 600 g, the amount of the additive used is 2-10 g.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the positive electrode material to the high entropy oxide is 100:(0.5-2); And / or, the temperature of the first sintering treatment and the second sintering treatment are each independently selected from 400-600° C.; And / or, the duration of the first sintering treatment and the second sintering treatment are each independently selected from 4-10 hours; And / or, the atmosphere of the first sintering treatment is an oxygen-containing atmosphere, preferably air; And / or, the atmosphere of the second sintering treatment is an inert atmosphere, preferably nitrogen.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The carbon source is not limited to glucose; and / or, the solvent includes but is not limited to at least one of water, methanol, and ethanol; And / or, the mass ratio of the high entropy oxide coating material, the carbon source, and the solvent is 1: (0.005-0.02): (0.4-0.8); and / or, the temperature of the solvent thermal reaction is 150-200° C.; And / or, the duration of the solvent thermal reaction is 20-60 min; And / or, the solvent thermal reaction is followed by solid-liquid separation and drying.

8. The preparation method according to claim 7, characterized in that: The temperature of the drying treatment is 80-150°C.

9. A double-coated modified positive electrode material, characterized in that: The double-coated modified positive electrode material is prepared by the preparation method of the double-coated modified positive electrode material described in any one of claims 1 to 8.

10. Use of the double-coated modified positive electrode material according to claim 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • Material for negative electrode of non-aqueous secondary battery, preparation method of material, non-aqueous secondary battery and negative electrode thereof

    CN102983318A

  • Method for preparing lithium nickel cobalt manganese oxide ternary cathode material in liquid-phase sugar coating and spray drying manners

    CN104733721A

  • Positive electrode material, preparation method thereof, positive electrode piece, and battery

    CN109817956A

  • Sodium-ion battery negative electrode material and preparation method and application thereof

    CN114477274A

  • Coated modified ternary positive electrode material and preparation method thereof

    CN114583147A

Cited By

  • Preparation method of high-entropy nanocapsule group and high-entropy lithium-rich manganese-based single crystal material

    CN120571515A

  • Preparation method of high-entropy nanocapsule group and high-entropy lithium-rich manganese-based single crystal material

    CN120571515B